Efficacy and safety of the pharmacotherapy used in the management of hyperkalemia: a systematic review - Varallo, Fabiana R.; Trombotto, Victoria [UNESP]; Lucchetta, Rosa C.; Mastroianni, Patricia de C. [UNESP] (Centro Investigaciones & Publicaciones Farmaceuticas, 2019)
Background: Although the management of hyperkalemia follows expert guidelines, treatment approaches are based on traditionally accepted practice standards. New drugs have been assessed such as sodium zirconium cyclosilicate and patiromer; however, their safety and efficacy or effectiveness have not yet been compared to traditional pharmacotherapy. Objective: The present systematic review had the purpose to evaluate the efficacy, effectiveness, and safety of hyperkalemia pharmacotherapies. Methods: PubMed, LILACS, Cochrane Library, and ClinicalTrials were searched through November 2018. Clinical trial, cohort and case-control were searched. The risk of bias (RoB v2.0 and ROBINS-I) and quality of evidence (GRADE) at the level of outcomes were assessed. Results: Sixteen clinical trials and one retrospective cohort were identified regarding efficacy and safety of 24 different alternatives. The management of hyperkalemia remains empirical and off-label, since sodium zirconium cyclosilicate and patiromer are not available in several countries and further studies are required to assess efficacy, effectiveness and safety. Sodium or calcium polystyrene sulfonate (moderate confidence), sodium zirconium cyclosilicate (moderate confidence), and insulin plus dextrose (moderate confidence) showed superior efficacy to, respectively, placebo, no treatment, placebo, and dextrose. Other therapies (low confidence) showed similar efficacy compared to active or inactive alternatives. Most of the adverse events reported were nonspecific, so it was not possible to assign the cause and to classify as defined or probable. Conclusions: Comparative cohort and case-control studies are need to evaluate the safety and effectiveness of new and traditional pharmacotherapies to support the development of guidelines about acute and chronic hyperkalemia, with high-quality evidence.
Keywords: Hyperkalemia; Potassium; Renal Insufficiency; Treatment Outcome; Silicates; Polymers; Systematic Reviews as Topic